Youth participation in religious activities: Case study of the Congregations of Mikael Agricola and Munkkiniemi Churches in Helsinki, Finland and Presbyterian Church Down Beach Limbe, Cameroon. A Comparative Perspective - Eyongakpa, Marie (My University, 2012)
This study explores the influence of culture on youth participation in three congregations; Mikael Agricola and Munkkiniemi in the Evangelical Lutheran Church, Finland and the Presbyterian Church Down Beach Limbe, Cameroon. The study hypothesized that youth in Mikael Agricola and Munkkiniemi congregations’ participation in the church is primarily for socialisation reasons while spiritual concept is secondary whereas, the reverse is seen in Presbyterian Church Down Beach Limbe, Cameroon. The methodology of the study was based on Charles. C.Ragins comparative case study method with qualitative perspective, with the use of a designed interview template to gather empirical data, and results analysed. Case study methods were used to denote the similarities and differences in the three congregations through their structure, policies and youth activities. The two main challenges were, getting data and materials from Cameroon and Finnish language barrier but I resorted to group interviews which were resourceful. The study explores the factors influencing youth attitudes towards the church, impact of church policies and it s implementation towards youth work, evaluating the degree of youth work through their active participation in church and recommendations for future youth work from youths, youth coordinators, pastors and some church authorities. The study result acknowledges three factors influencing youth’s participation in the church, the church structure, policy and its implementation and culture.
Keywords: Church; Youths; Participation; Mikael Agricola; Munkkiniemi; Presbyterian Church Down Beach Limbe; Culture and Spiritual.; fi=Viestintätieteet|en=Communication Studies|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|